marA efflux pump gene expression in Salmonella enteritidis strains treated with Artemisia tournefortiana hydroalcoholic extract and comparison with commercial efflux pump inhibitor, carbonyl cyanide 3-chlorophenylhydrazone (CCCP) - Khosravani, Marjan; Soltan Dallal, Mohammad Mehdi; Norouzi, Mehdi (Archives of Medical Laboratory Sciences, 2020)
Background: Salmonella enterica subsp. enterica serovar Enteritidis is a food-borne pathogenic bacterium that has recently become resistant to most quinolone antibiotics. The MarA efflux pump plays a significant role in the development of ciprofloxacin resistance in S. Enteritidis strains. The aim of this study was comparative evaluation of anti-efflux activity of Artemisia tournefortiana extract and commercial efflux inhibitor, carbonyl cyanide 3-chlorophenylhydrazone (CCCP) on marA efflux pump gene expression in S. Enteritidis clinical strains. Materials and Methods: In this experimental study, Artemisia tournefortiana extract was prepared using maceration method. Subsequently, MarA efflux pump was detected in 20 clinical strains of S. Enteritidis via cartwheel and PCR methods. Finally, after treatment of strains with subMIC concentration of extract and 20 µg/L and CCCP, their anti-efflux activity against MarA efflux pump was studied using Real Time PCR. Results: The results of cartwheel and PCR methods indicated that all of ciprofloxacin resistant strains had MarA efflux pump. Subsequently, after treatment of strains with subMIC concentration of extract and CCCP, results show that both component have the ability to inhibit the MarA efflux pump, significantly. Conclusion: Considering the results of MarA efflux inhibition by A. tournefortiana and CCCP, it seems that this plant can be used as a potential source of drug use as a suppository pump inhibitor instead of CCCP.